Clinical-pathological study of Equine Sarcoid Fibroblastic: clinical case report - Pinilla León, Juan Carlos (2019)
The case is described in a 6-year-old Colombian Paso Fino equine that presents a recurrent mass of irregular, granulomatous, ulcerative and hemorrhagic appearance in the prepuce and penis region. Surgical resolution of the tumor, histopathological study and postoperative treatment of the equine were performed. The macroscopic characteristics and histological description of the lesions studied showed the presence of a fibroblastic Sarcoid type.